When the Wolf Came : The Civil War and the Indian Territory - Warde, Mary Jane, 1944- (Book collections on Project MUSE., 2013)
Winner of the 2014 Oklahoma Book Award for nonfiction Winner of the 2014 Pate Award from the Fort Worth Civil War Round Table. When the peoples of the Indian Territory found themselves in the midst of the American Civil War, squeezed between Union Kansas and Confederate Texas and Arkansas, they had no way to escape a conflict not of their choosing--and no alternative but to suffer its consequences. When the Wolf Came explores how the war in the Indian Territory involved almost every resident, killed many civilians as well as soldiers, left the country stripped and devastated, and cost Indian n.